Characteristics of new flue-cured tobacco strains developed from Yunyan87 mutants and their DNA fingerprint identification - CHEN Tingting; LI Xianfu; JIA Chunlei; AN Xueqin; ZHU Jun; XIAO Lizeng; DAI Xiumei; ZHANG Jiankui (浙江大学学报. 农业与生命科学版)
Yunyan87 was a flue-cured tobacco variety with largest-scale cultivation in China. To further improve the yield and quality of Yunyan87, two new mutant strains named T24 and Aoyeyan were developed from the natural mutants of Yunyan87 using selection breeding method. The characteristics and DNA fingerprint of the two new mutant strains were identified to provide basis for variety application, identification and protection.The field tests were performed to identify the botanic characters, agronomic characteristics, yield and quality of T24 and Aoyeyan in Tongren City of Guizhou Province from 2011 to 2013, using the leading flue-cured tobacco cultivars Yunyan87 and K326 as control varieties. Furthermore, simple sequence repeat (SSR) molecular marker technology was used to establish the DNA fingerprint maps of T24, Aoyeyan and their genetically related varieties Yunyan87, K326, Yunyan97 and four new mutant lines and strains (M97-1, Pianpianhuang, 09-1, Ketianyan), altogether nine accessions.The results were as follows: 1) The botanic characteristics, plant shape and growth duration in field of T24 and Aoyeyan were similar with Yunyan87, but their effective leaf numbers, leaf length and width, stem circumference, plant height all exceeded Yunyan87. The yields of T24 and Aoyeyan were 2 247.38 and 2 195.62 kg/hm2, with production value of 53 657.56 and 52 586.47 Yuan RMB/hm2, and the rates of superior and middle grade leaves were 90.59% and 90.38%, respectively, which all exceeded control varieties. The contents of reducing sugar, total sugar, starch, total plant nicotine of T24 and Aoyeyan were all up to the high quality standard of flue-cured tobacco leaves. The sensory taste score of T24 was 80.0, higher than Yunyan87 and K326, with scores of 76.3 and 77.7, respectively. The sensory taste score of Aoyeyan was 75.3.2) Four SSR primers, i.e. PT20213, PT30028, PT30224 and PT30399 were selected from 14 core primers, which gave stable and polymorphic amplification profiles and had efficient identification ability to tobacco varieties. Eighteen polymorphic DNA fragments of all nine varieties including T24, Aoyeyan, Yunyan87, K326, Yunyan97, M97-1, Pianpianhuang, 09-1, Ketianyan were amplified, among which seven specific bands were selected to encode the fingerprint database. Fingerprint map of the nine varieties were drawn according to the fingerprint database. Each variety had a distinctive fingerprint map, therefore could be identified each other by at least three SSR primers, and the identification process of the nine varieties was established.In conclusion, the yield and quality of T24 are higher than Yunyan87, so T24 has a great application potential. The distinctive fingerprint map of the tested varieties can provide basis for the variety identification and protection.